2016
DOI: 10.1007/s11548-016-1385-4
|View full text |Cite
|
Sign up to set email alerts
|

Robust augmented reality guidance with fluorescent markers in laparoscopic surgery

Abstract: As the concept can be smoothly integrated into the clinical workflow, its potential for application in clinical laparoscopy is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Several studies reported using a set of infrared markers [ 4 , 10 , 13 , 33 , 37 40 ]. A newer approach suggested by Wild et al [ 41 ] involved using fluorescent markers during laparoscopic procedures. The main advantage of such markers is the clear visibility even in difficult conditions and the ability to remain in the patient after the surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported using a set of infrared markers [ 4 , 10 , 13 , 33 , 37 40 ]. A newer approach suggested by Wild et al [ 41 ] involved using fluorescent markers during laparoscopic procedures. The main advantage of such markers is the clear visibility even in difficult conditions and the ability to remain in the patient after the surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The main advantage of such markers is the clear visibility even in difficult conditions and the ability to remain in the patient after the surgery. However, this requires an endoscopic system capable of detecting the emitted light [ 41 ]. Konishi et al proposed an electromagnetic tracking system paired with an infrared sensor for laparoscopic surgery [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…6,9,21,22 Of these methods, visionbased tracking seems to be optimally suited for fluorescence cameras when combined with (fluorescent) skin fiducials, detectable with the camera. 23 Most realistically a combination of tracking technologies will provide outcome. 24,25 Next to the fluorescence cameras that are currently available in the clinic, this research also supports the navigation of future surgical fluorescence imaging devices; e.g., fluorescence goggles and head-mounted displays.…”
Section: Discussionmentioning
confidence: 99%
“…A safe and practical tracking technique to acquire realtime information on tumor position is electromagnetic (EM) tracking of EM sensors that are implanted in or around the tumor [9]. This technique does not require a radiation dose or line-of-sight, as opposed to alternatives such as intraoperative computational tomography (CT) and the use of optical markers [10][11][12]. EM tracking has been studied in a variety of fields, including surgery [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%